Pengembangan Aplikasi Sistem Informasi Janji Temu dengan Dokter (E-Doc) Berbasis Web untuk Mengurangi Waktu Tunggu Pasien di Rumah Sakit Umum Nurul Hasanah - Sambo, Sri Wahyuni; Damayanti, Yusnika; Nasution, Guslila Sari; Alacsel, Sanjaya; Jaya, Fitra (SAFE-Network, 2024)
This research to develop a WEB-based Doctor Appointment Information System Application (E-Doc) at the Nurul Hasanah General Hospital which is useful for reducing patient waiting times. The use of this application is expected to increase the efficiency of the registration process and meetings between patients and doctors, by allowing patients to make appointments online, choose a doctor's schedule, and find out the available queue quota. The methods used in this research include literature and interviews as well as system requirements analysis, application design, as well as implementation and evaluation of application use by patients and medical personnel. The research results show that the E-Doc application can speed up the registration process and reduce queues at the Nurul Hasanah General Hospital, so that patients can access health services more efficiently. Apart from that, this application makes it easy for patients who face geographical or physical obstacles to get services without having to come directly to the hospital to register. Thus, it is hoped that the development of this application can improve the quality of health services and minimize patient waiting times at the Nurul Hasanah General Hospital.